GE_GERICHTE P/2271/2019 vom 30. März 2023 - GE Cour de justice (2023)
VIOLENCE DOMESTIQUE;CONTRAINTE(DROIT PÉNAL);ENLÈVEMENT(INFRACTION);INFRACTIONS CONTRE L'HONNEUR;LÉSION CORPORELLE;EXPULSION(DROIT PÉNAL);MAXIME OFFICIELLE | CP.123.ch1; CP.181; CP.177.al1; CP.183; CP.123.ch2